Exploring Lexical Density in the New York Times - Farida Repelita Kembaren; Ade Novira Aswani (ELLITE, 2022)
The goal of the study was to evaluate the lexical density and readability of five news articles from The New York Times. A qualitative content analysis methodology was employed in conducting the research. Methods from Ure (1971) and Halliday (1985) were used to analyze the lexical density, and Flesch’s (1948) Reading Ease Score and Grade Level were used to evaluate the readability of the news articles. The findings showed that The New York Times news articles had lexical densities that were higher than 50%, significantly lower readability scores than 50, and grade levels greater than 12.The percentages of lexical density were higher than Ure’s (1971) minimum score for written texts. The readability score also revealed that the news articles required a high level of reading comprehension and were best understood by readers who were at least 18 years old or at least in college. The study came to the conclusion that The New York Times is one of the most trustworthy and reputable news sources.